Use of Dead Mussel Shells by Madtom Catfishes in the Green River - Jacob F Brumley; Philip W. Lienesch (Southeastern Fishes Council Proceedings, 2020)
The Green River in Kentucky has high fish and macroinvertebrate diversity. As both fish and macroinvertebrates have evolved together in this system, relationships have developed between species. One type of relationship that has been observed is between madtom catfishes (Noturus spp.) and mussels in the Green River, where madtoms use dead mussel shells as cover when not actively foraging. In the fall of 2016 and 2017, surveys were conducted to determine if madtom catfishes use dead mussel shells more than rocks of similar size. We predicted that madtoms would select mussel shells as cover more frequently than rocks due to the natural concavity of mussel shells, which would not require excavation prior to use; rocks typically require removal of underlying substrates to create a cavity prior to use as cover. Three 12-meter by 12-meter plots were sampled at four sites along the Green River, once per year, by snorkeling in an upstream direction and searching for madtoms in dead mussel shells and under the rock substrate. Equal effort was used searching for madtoms under rocks and in mussel shells. Significantly more madtoms were found under mussel shells than under rocks of similar size. These results support our prediction and demonstrate the importance of mussel shells as cover for madtom catfishes. The decline of mussel populations, and resulting decline in available mussel shells in rivers and streams, may have negative effects on madtom populations in the future.
Keywords: Madtom catfishes; mussel shells; cover